Pass the popcorn: "Obesogenic" behaviors and stigma in children's movies. (6th December 2013) - Throop, Elizabeth M.; Skinner, Asheley Cockrell; Perrin, Andrew J.; Steiner, Michael J.; Odulana, Adebowale; Perrin, Eliana M.
<x xml:space="preserve">Abstract</x> Objective To determine the prevalence of obesity‐related behaviors and attitudes in children's movies. Methods A mixed‐methods study of the top‐grossing G‐ and PG‐rated movies, 2006‐2010 (4 per year) was performed. For each 10‐min movie segment, the following were assessed: 1) prevalence of key nutrition and physical activity behaviors corresponding to the American Academy of Pediatrics obesity prevention recommendations for families; 2) prevalence of weight stigma; 3) assessment as healthy, unhealthy, or neutral; 3) free‐text interpretations of stigma. Results Agreement between coders was >85% (Cohen's kappa = 0.7), good for binary responses. Segments with food depicted: exaggerated portion size (26%); unhealthy snacks (51%); sugar‐sweetened beverages (19%). Screen time was also prevalent (40% of movies showed television; 35% computer; 20% video games). Unhealthy segments outnumbered healthy segments 2:1. Most (70%) of the movies included weight‐related stigmatizing content (e.g., "That fat butt! Flabby arms! And this ridiculous belly!"). Conclusions These popular children's movies had significant "obesogenic" content, and most contained weight‐based stigma. They present a mixed message to children, promoting unhealthy behaviors while stigmatizing the behaviors' possible effects. Further research is needed to determine the effects of such messages on children.